Kontribusi Persepsi Keharmonisan Keluarga terhadap Problematic Internet Use pada Remaja - Amalia Kartika Yani; Maya Yasmin (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The use of the internet has many benefits and also makes it easier for someone to do their work, besides the positive benefits, if it is used inappropriately it will trigger problems such as problematic internet use. Problematic internet use according to demetrovis et al (2008) is a condition where someone has difficulty controlling internet use. One of the factors causing problematic internet use is the family harmony. The purpose of this study was to analyze the contribution of perceptions of family harmony to problematic internet use in adolescents in West Sumatra with 400 respondents. This research uses a quantitative method study with cluster sampling technique. Problematic internet use and family harmony were measured using a measuring instrument compiled by researchers based on aspects of demetrovics et al (2008) for problematic internet use and kavikondala et al (2016) for family harmony. Based on the results of a analysis simple linear regression, an value of r square is 0.088 was obtained, indicating that family harmony contributed to problematic internet use in adolescents by 8.8%.